2020
DOI: 10.1016/j.gie.2019.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and clinical outcomes of endoscopic dilation in benign esophageal strictures: a long-term follow-up study

Abstract: Background and Aims: Endoscopic dilation (ED) is still the mainstay of therapeutic management of benign esophageal strictures (BESs). This study aimed to establish risk factors for refractory BESs and assess longterm clinical outcomes of ED.Methods: We performed a retrospective study in 891 patients who underwent ED from 2003 to 2018 for BESs. We searched electronic medical records in 6 tertiary care centers in the Netherlands for data on clinical outcome of ED. Median follow-up was 39 months. The primary endp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Review of studies which included greater than 100 patients with benign upper GI strictures, either anastomotic, achalasia, post-ESD, eosinophilic, gastric outlet obstruction or mixed aetiology, reveals a risk of haemorrhage well below 1%. [131][132][133][134][135][136][137][138][139][140] A systematic review and meta-analysis of studies of endoscopic dilatation of gastroduodenal Crohn's disease strictures revealed a 2.1% per procedure risk of haemorrhage. 141 In a prospective study of dilatation in 55 patients with oesophageal carcinoma no clinically relevant haemorrhage was observed.…”
Section: Endoscopic Dilatationmentioning
confidence: 99%
“…Review of studies which included greater than 100 patients with benign upper GI strictures, either anastomotic, achalasia, post-ESD, eosinophilic, gastric outlet obstruction or mixed aetiology, reveals a risk of haemorrhage well below 1%. [131][132][133][134][135][136][137][138][139][140] A systematic review and meta-analysis of studies of endoscopic dilatation of gastroduodenal Crohn's disease strictures revealed a 2.1% per procedure risk of haemorrhage. 141 In a prospective study of dilatation in 55 patients with oesophageal carcinoma no clinically relevant haemorrhage was observed.…”
Section: Endoscopic Dilatationmentioning
confidence: 99%
“…Review of studies which included greater than 100 patients with benign upper GI strictures, either anastomotic, achalasia, post-ESD, eosinophilic, gastric outlet obstruction or mixed etiology, reveals a risk of haemorrhage well below 1 % 131 132 133 134 135 136 137 138 139 140 . A systematic review and meta-analysis of studies of endoscopic dilatation of gastroduodenal Crohn’s disease strictures revealed a 2.1 % per procedure risk of haemorrhage 141 .…”
Section: Endoscopic Proceduresmentioning
confidence: 99%
“…We read with interest the letter by Doctor et al 1 and would like to respond to their concerns. Their first concern is related to not following the rule of 3 because it may increase the risk of esophageal perforation.…”
Section: Responsementioning
confidence: 99%